Gut Bacterial Diversity in Different Life Cycle Stages of Adelphocoris suturalis (Hemiptera: Miridae) - Xue, Hui; Zhu, Xiangzhen; Wang, Li; Zhang, Kaixin; Li, Dongyang; Ji, Jichao; Niu, Lin; Wu, Changcai; Gao, Xueke; Luo, Junyu; Cui, Jinjie (Frontiers in Microbiology, 2021)
Bacteria and insects have a mutually beneficial symbiotic relationship. Bacteria participate in several physiological processes such as reproduction, metabolism, and detoxification of the host. Adelphocoris suturalis is considered a pest by the agricultural industry and is now a major pest in cotton, posing a serious threat to agricultural production. As with many insects, various microbes live inside A. suturalis. However, the microbial composition and diversity of its life cycle have not been well-studied. To identify the species and community structure of symbiotic bacteria in A. suturalis, we used the HiSeq platform to perform high-throughput sequencing of the V3 – V4 region in the 16S rRNA of symbiotic bacteria found in A. suturalis throughout its life stages. Our results demonstrated that younger nymphs (1st and 2nd instar nymphs) have higher species richness. Proteobacteria (87.06%) and Firmicutes (9.43%) were the dominant phyla of A. suturalis. At the genus level, Erwinia (28.98%), Staphylococcus (5.69%), and Acinetobacter (4.54%) were the dominant bacteria. We found that the relative abundance of Erwinia was very stable during the whole developmental stage. On the contrary, the relative abundance of Staphylococcus, Acinetobacter, Pseudomonas, and Corynebacterium showed significant dynamic changes at different developmental stages. Functional prediction of symbiotic bacteria mainly focuses on metabolic pathways. Our findings document symbiotic bacteria across the life cycle of A. suturalis, as well as differences in both the composition and richness in nymph and adult symbiotic bacteria. Our analysis of the bacteria in A. suturalis provides important information for the development of novel biological control strategies.